2016
DOI: 10.1038/srep25455
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Kondo-like Scattering at the SrTiO3-based Interfaces

Abstract: The observation of magnetic interaction at the interface between nonmagnetic oxides has attracted much attention in recent years. In this report, we show that the Kondo-like scattering at the SrTiO3-based conducting interface is enhanced by increasing the lattice mismatch and growth oxygen pressure PO2. For the 26-unit-cell LaAlO3/SrTiO3 (LAO/STO) interface with lattice mismatch being 3.0%, the Kondo-like scattering is observed when PO2 is beyond 1 mTorr. By contrast, when the lattice mismatch is reduced to 1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 48 publications
4
38
0
Order By: Relevance
“…Han et al [401] reported weaker Kondo signatures in samples that were expected to have a higher concentration of oxygen vacancies (growth at lower oxygen partial pressure without post annealing). The explanation was that in the samples with more oxygen vacancies, the conduction networks extended into the bulk and were able to evade the dilute local moments, resulting in the weaker coupling between the iterant carriers and localized moments [401].…”
Section: Kondo Effectmentioning
confidence: 99%
“…Han et al [401] reported weaker Kondo signatures in samples that were expected to have a higher concentration of oxygen vacancies (growth at lower oxygen partial pressure without post annealing). The explanation was that in the samples with more oxygen vacancies, the conduction networks extended into the bulk and were able to evade the dilute local moments, resulting in the weaker coupling between the iterant carriers and localized moments [401].…”
Section: Kondo Effectmentioning
confidence: 99%
“…The sample had 12 monolayers of LSAT deposited on (111) oriented STO using pulsed laser deposition, at a growth partial oxygen pressure of 10 −4 Torr. 31,32 No post growth annealing step was performed. Ti/Au was deposited on contact pads of the Hall bars, and Al wirebonds were made to allow for a 4-probe measurement of transverse and longitudinal resistance.…”
mentioning
confidence: 99%
“…Earlier work on (001) LAO/STO interfaces 15 demonstrated that strain at the interface can drastically change conduction, whereas recent studies of LSAT grown on (001) STO suggested that the lower strain compared to LAO significantly increased the carrier mobility. 24,29 However, there have been only a few transport experiments performed on LSAT/STO interfaces to date, and none on (111) oriented LSAT/STO. In particular, the effect of an electric field, which has proved to be a powerful tool to probe the properties of other STO based interface devices, has not been studied in the case of LSAT/STO.…”
mentioning
confidence: 99%